Tonga : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix reviews the past conduct of monetary policy of Tonga. The paper considers the problems in the current system and discusses the policy options available to the authorities. It reviews Tonga's exchange rate policy and explores its effectiveness in light of the economy's structure and macroeconomic developments. The paper also discusses some of the key features of the framework supporting the Tonga Trust Fund. Its main shortcomings are assessed in light of the best international practices and some lessons for the future are discussed.